Sarcopenia for predicting mortality among elderly nursing home residents: SARC-F versus SARC-CalF - Yang, Ming (Medicine (Baltimore), 2019)
Little is known about the prognostic value of the strength, assistance walking, rise from a chair, climb stairs, and falls questionnaire (SARC-F) and SARC-F combined with calf circumference (SARC-CalF) among elderly nursing home residents. To compare the prognostic value of SARC-F and SARC-CalF for mortality in this population. We conducted a prospective study in four nursing homes in western China. Sarcopenia was estimated using SARC-F and SARC-CalF, respectively. Nutrition status, activities of daily living, and other covariates were evaluated. The survival status was collected via medical records and telephone interviews at the 12th month after the baseline investigation. We used multivariate Cox proportional-hazard models to calculate the hazard ratio (HR) and 95% confidence interval (CI) for 1-year all-cause mortality by SARC-F-defined sarcopenia and SARC-CalF-defined sarcopenia, separately. We included 329 participants (median age: 85 years). The prevalences of SARC-F-defined sarcopenia and SARC-CalF-defined sarcopenia were 39.8% and 46.8%, respectively. During the 1-year follow-up period, 73 participants (22.7%) died. The mortality was 29.0% and 18.3% in the participants with or without SARC-F-defined sarcopenia, respectively (P = .025). The mortality was 26.6% and 19.0% in the participants with or without SARC-CalF-defined sarcopenia, respectively (P = .105). After adjusted for the relevant confounders including malnutrition, SARC-F-defined sarcopenia was independently associated with an increased risk of 1-year mortality (adjusted HR: 2.08; 95% CI: 1.27–3.42). However, SARC-CalF-defined sarcopenia was not an independent predictor of 1-year mortality (adjusted HR: 1.54; 95% CI: 0.95–2.47). Sarcopenia is highly prevalent in Chinese elderly nursing home residents according to SARC-F or SARC-CalF. SARC-F-defined sarcopenia appears to be better for predicting the 1-year mortality of Chinese nursing home residents than SARC-CalF-defined sarcopenia.